Positive experiences among elite athletes in Finland: associations with basic psychological needs, sport conditions, and background factors - Kaski, S.; Kinnunen, U. (Journal of Clinical Sport Psychology, 2026)
This research aimed to study the prevalence of PERMA experiences (Positive emotions, Engagement, (positive) Relationships, Meaning, and Accomplishment) among elite athletes in Finland (n = 2,045) and factors that are potentially connected to these experiences. The results indicated that, depending on the PERMA component, 40%-52% of the athletes had positive experiences in sports. A total of 42% of the athletes could be classified as flourishing. Feeling competent in sports was positively related to all PERMA experiences. The safe atmosphere of the team seemed to be of greater importance for PERMA components than coach behavior. Belonging to a minority group was negatively related to all positive experiences except for Engagement. Our results suggest that strengthening of athletes` feeling of competence is essential in promoting positive experiences in sports, which are important for athletes` functioning and success. In addition, sports organizations should pay more attention to how to strengthen equality and equity in sports.